The Features of the Concept of Generosity in English and Uzbek Phraseological Units (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this scientific article, it is noted that in the past, children from families that owned horses began to learn horsemanship from a young age. In the books of some pre-revolutionary authors, it was mentioned that Uzbeks put boys on horseback from the age of five, and by the age of ten, they participated in combat games and horse races. Written sources indicate that not only Uzbek men but also women were skilled in horse riding.